Intracystic Papillary Carcinoma in the Male Breast: A Rare Endpoint of a Wide Spectrum. (26th August 2013) - Vagholkar, Ketan; Dastoor, Khojasteh; Gopinathan, Indumati
Abstract : Introduction . Fibrocystic disease of the male breast is uncommon. The presence of a spectrum of changes ranging from fibrocystic disease to duct papilloma to papillary carcinoma in the same patient renders the case a rarity and therefore reportable. Case Report . A case of intracystic papillary carcinoma of the male breast is presented. Discussion . The pathological, clinical, diagnostic, and therapeutic options are discussed after reviewing the literature. Conclusion . Modified radical mastectomy with axillary clearance is the safest option for established cases.